2002
DOI: 10.1021/jf025697h
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Flavonoid Compounds in Rooibos Tea (Aspalathus linearis) by LC−UV/DAD

Abstract: Rooibos tea originates from the leaves and stems of the indigenous South African plant Aspalathus linearis. It has gained much attention for clinical purposes in the case of nervous tension, allergies (dermatitis), and various indigestive problems. Recently, antioxidative activity was also attributed to the tea on the basis of its flavonoid content. Therefore, an HPLC method using a C(18) reversed phase column was developed for the assay of 10 flavonoids in aqueous and methanolic infusions. Main compounds dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 10 publications
4
93
0
Order By: Relevance
“…These isomeric compounds are reported to be interconvertable via a Wessely-Moser rearrangement of the flavone structure under heating in an aqueous solution: conditions similar to those that occur during tisane extraction (Koeppen and Roux, 1965). They are extractable in hot aqueous media from commercial fermented rooibos tea at 1.00 and 0.83 g kg -1 respectively; comparable to the aspalathin extracted in the same manner (1.23 g kg -1 ) (Bramati et al, 2002). The flavones vitexin and isovitexin are also present in rooibos tea, however are significantly less abundant than the aforementioned compounds (0.33 and 0.27 g kg -1 respectively).…”
Section: IV Edible Leaves and Stemsmentioning
confidence: 89%
See 2 more Smart Citations
“…These isomeric compounds are reported to be interconvertable via a Wessely-Moser rearrangement of the flavone structure under heating in an aqueous solution: conditions similar to those that occur during tisane extraction (Koeppen and Roux, 1965). They are extractable in hot aqueous media from commercial fermented rooibos tea at 1.00 and 0.83 g kg -1 respectively; comparable to the aspalathin extracted in the same manner (1.23 g kg -1 ) (Bramati et al, 2002). The flavones vitexin and isovitexin are also present in rooibos tea, however are significantly less abundant than the aforementioned compounds (0.33 and 0.27 g kg -1 respectively).…”
Section: IV Edible Leaves and Stemsmentioning
confidence: 89%
“…These unusual compounds have received a significant deal of attention, not least because of their abundance in this tisane and the importance of this principal South African export to its home economy. Indeed, the routine quantification of both aspalathin (2 ,3,4,4 ,6 -pentahydroxy-3-C--Dglucopyranosyldihydrochalcone) and the 2 ,4,4 ,6 tetrahydroxylated analogue, nothofagin, has become an accepted measure of rooibos quality, with several publications detailing methodologies for analysis and abundance in material from various processing yards and following several processing protocols (Bramati et al, 2003;Bramati et al, 2002;Joubert, 1996;Joubert and deVilliers, 1997;Joubert et al, 2008;Manley et al, 2006;Pengilly et al, 2008;Rabe et al, 1994;Schulz et al, 2003;Standley et al, 2001;vonGadow et al, 1997). The predominant factor determining the concentration of these two C-glycosyl dihydrochalcones in rooibos tea is the 'fermentation' process.…”
Section: IV Edible Leaves and Stemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, aspalathin (Asp), a major flavonoid in rooibos, is present at twice the level in unfermented compared to fermented tea (Bramati et al, 2002, Bramati et al, 2003. Asp is a dihydrochalcone-C-glucoside and has been reported to ameliorate hyperglycemia (Kawano et al, 2009, Muller et al, 2012, Son et al, 2013.…”
Section: Rooibos (Aspalathus Linearis) Is a Leguminous Shrub Native Tomentioning
confidence: 99%
“…It is naturally caffeine-free and has low tannin content when compared to Camellia sinensis teas, but high in unique antioxidant polyphenols (Joubert et al, 2008). Rooibos has a flavonoid profile that is distinctly different from those found in Camellia sinensis, including the β-dihydroxy-dihydrochalcone glucoside aspalathin, and its cyclic counterpart aspalalinin, both of which are unique to rooibos (Rabe et al, 1994;Shimamura et al, 2006), the dihydrochalcone nothofagin, as well as flavonols including orietin, iso-orientin, vitexin, isovitexin, luteolin, quercetin and chrysoeriol among others (Rabe et al, 1994;Bramati et al, 2002;Joubert et al, 2008). Studies has shown that rooibos exert hepatoprotective effect in acute and chronic liver damage in rats (Ulicna et al, 2003;, and modulate oxidative stress by preventing lipid peroxidation and improving glutathione redox status in rat tissues and in humans (Nikolova et Red palm oil (RPO) is the edible oil obtained from crude palm oil extracted from the oil palm plant, (Elaeis guineesis), after a modified refining process, involving degumming and bleaching, followed by de-acidification and deodorisation by molecular distillation (Nagendran et al,200).…”
Section: Introductionmentioning
confidence: 99%